Impact of the single point of access referral system to reduce waiting times and improve clinical outcomes in an assistive technology service. (3rd July 2016) - Hosking, Jonathan; Gibson, Colin
Abstract: The introduction of a single point referral system that prioritises clients depending on case complexity and overcomes the need for re-admittance to a waiting list via a review system has been shown to significantly reduce maximum waiting times for a Posture and Mobility (Special Seating) Service from 102.0 ± 24.33 weeks to 19.2 ± 8.57 weeks ( p  = 0.015). Using this service model linear regression revealed a statistically significant improvement in the performance outcome of prescribed seating solutions with shorter Episode of Care completion times ( p  = 0.023). In addition, the number of Episodes of Care completed per annum was significantly related to the Episode of Care completion time ( p  = 0.019). In conclusion, it is recommended that it may be advantageous to apply this service model to other assistive technology services in order to reduce waiting times and to improve clinical outcomes.